Distance to water source and altitude in relation to active trachoma in Rombo district, Tanzania - Baggaley, R. F. (Trop Med Int Health, 2006)
OBJECTIVES: To investigate the relationship between distance to water source, altitude and active trachoma in children in Rombo district, Tanzania. METHODS: In each of Rombo’s 64 villages, 10 balozis (groups of 8–40 households) were selected at random and all resident children aged 1–9 years were examined for clinical signs of active trachoma. The households of these children and village water sources were mapped using differentially corrected global positioning system data to determine each household’s altitude and distance to the nearest water supply. RESULTS: We examined 12 415 children and diagnosed 1171 cases of active trachoma (weighted prevalence = 9.1%, 95% CI: 8.0, 10.2%). Active trachoma prevalence ranged from 0% to 33.7% across villages. Increasing distance to the nearest water source was significantly associated with rising trachoma prevalence (age-adjusted odds ratio for infection (OR) for highest quartile compared to lowest = 3.56, 95% CI 2.47, 5.14, P for trend <0.0001). Altitude was significantly inversely associated with trachoma prevalence (age-adjusted OR for highest quartile compared to lowest = 0.55, 95% CI 0.41, 0.75, P for trend <0.0001). These associations remained significant after adjustment in multivariate analysis. CONCLUSIONS: Trachoma is endemic in Rombo district, although the prevalence varies considerably between villages. Spatial mapping is a useful method for analysing risk factors for active trachoma.